KUIS SEBAGAI SARANA EDUKASI YANG EFEKTIF DAN MENYENANGKAN UNTUK MENINGKATKAN LITERASI GIZI PADA APARATUR SIPIL NEGARA (ASN) PUSAT YANG DITEMPATKAN DI DAERAH - Warnaini, Cut; Suryantini, Ni Kadek Mega (Universitas Mataram, 2024)
The higher number of placements of the central State Civil Apparatus and families in new areas that have never been recognized or visited before, can trigger changes experienced, especially adjustments in meeting the nutrients obtained by adjusting to the typical culture of the region. This will be a challenge for both the central State Civil Apparatus itself or with his family, because adaptation is needed again to the new area and environment. Increase knowledge and awareness related to nutrition for central State Civil Apparatus and Families stationed in the regions. The implementation method used was the “Family 100” quiz. The implementation of the “Family 100” quiz is divided into two groups of four people in each group. The quiz is divided into three rounds, namely the general round, quiz, and bonus round which will be guided by a moderator. The task of each group was to collect as many scores as possible from each round to find the winner. Participants enthusiastic in participating in this activity in obtaining information about nutrition. The scores of the two groups that played were high. The accumulated score of the 3 rounds received by group 1 amounted to 2,830 and group 2 amounted to 2,160. In general, the participants' knowledge in nutrition is good, but from the specific knowledge of nutritional information and the benefits contained in food ingredients is still lacking, this can be seen from some questions that cannot be answered by each group.Through this activity participants can increase knowledge and awareness regarding nutrition and change behavior to live a healthy life.